PENGEMBANGAN KOMPETENSI GURU UNTUK MEMPERKUAT MUTU KERJA LEMBAGA PENDIDIKAN ISLAM - Muhammad Ali Murtadho; Zainal Berlian; Baharuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine teacher competency development in strengthening the work quality of Islamic educational institutions. The research employed a qualitative approach using a library research method. Data were collected from books, scientific journals, and relevant studies, then analyzed using content analysis techniques. The findings show that teacher competency development is carried out through training, workshops, continuing education, teacher forums (MGMP), and spiritual as well as personality development programs. Supporting factors include institutional policies, leadership, conducive work environments, and the use of technology, while inhibiting factors include limited facilities, high workloads, low motivation, and unsustainable programs. Teacher competency development significantly affects learning quality, teacher performance, and the overall work quality of Islamic educational institutions. Therefore, teacher competency development should be implemented systematically and sustainably as a strategy to improve the quality of Islamic education.